2021
DOI: 10.1002/bit.27732
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining of Streptomyces sp. CB00271 as a natural high‐producer of β‐rubromycin and the resulting discovery of β‐rubromycin acid

Abstract: β-rubromycin (β-RUB) ( 1) is an efficient inhibitor of human telomerase possessing a unique spiroketal moiety as a potential pharmacophore and regarded as a promising anticancer drug lead. But the development of (β-RUB) (1) has long been hampered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In our previous studies, CB04723 has already been identified as a producer of griseorhodins . Besides griseorhodin A and griseorhodin C, there were several other metabolites produced by CB04723 in MIE medium (Figure B).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous studies, CB04723 has already been identified as a producer of griseorhodins . Besides griseorhodin A and griseorhodin C, there were several other metabolites produced by CB04723 in MIE medium (Figure B).…”
mentioning
confidence: 80%
“…In our previous studies, CB04723 has already been identified as a producer of griseorhodins. 36 Besides griseorhodin A and griseorhodin C, there were several other metabolites produced by CB04723 in MIE medium (Figure 1B). Based on UV absorption and molecular weight (Figure S5), these six major metabolites could be divided into two groups (Figure 1B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CB00271, a high-yield producing strain of β-rubromycin and a new congener βrubromycin acid through a genome mining approach. 26 A green compound named chalkophomycin (CHM, 1) was isolated from the fermentation broth of S. sp. CB00271 with the addition of microporous resins (Figures S4−S9).…”
mentioning
confidence: 99%
“…We have previously discovered S. sp. CB00271, a high-yield producing strain of β-rubromycin and a new congener β-rubromycin acid through a genome mining approach . A green compound named chalkophomycin (CHM, 1 ) was isolated from the fermentation broth of S. sp.…”
mentioning
confidence: 99%